Bacterial microbiome variation across symbiotic states and clonal lines in a cnidarian model - Curtis, Ezra; Moseley, Joanne; Racicot, Riccardo; Wright, Rachel M. (Frontiers in Marine Science, 2023)
Exaiptasia diaphana is a popular model organism for exploring the symbiotic relationship observed between cnidarians and their microsymbionts. While physiological roles of algal photosymbionts (Symbiodinaceae) are well studied, the contributions of bacterial communities are less defined in this system. We investigated microbial variation between distinct parts of the body and symbiotic state across four genets held in identical environmental conditions using 16s rRNA gene amplicon sequencing. We found differentially abundant taxa between body part and symbiotic state that highlight the roles these bacteria may play in holobiont heterotrophy and nutrient cycling. Beta-diversity analysis revealed distinct communities between symbiotic states consistent with previous studies; however, we did not observe the presence of previously reported core microbiota. We also found community differences across clonal lines, despite years of identical rearing conditions. These findings suggest the Exaiptasia bacterial microbiome is greatly influenced by host genetics and unpredictable environmental influences.